Answer:it is d i hope that helps
Step-by-step explanation:
3n - 1
When n = 1,
3n - 1 = 3*1 - 1 = 3 -1 = 2
When n = 2,
3n - 1 = 3*2 - 1 = 6 -1 = 5
When n = 3,
3n - 1 = 3*3 - 1 = 9 -1 = 8
Hence, the first three terms are 2, 5 and 8.
You take the 3 squared which is 9 then, you divide that by three then you get 3
The first derivative of the function f(x) = x² - 5 is equal to f'(x) = 2 · x.
<h3>How to find the derivative of a quadratic equation by definition of derivative</h3>
In this question we have a quadratic function, in which we must make use of the definition of derivative to find the expression of its first derivative. Then, the procedure is shown below:
f(x) = x² - 5 Given
f' = [(x + h)² - 5 - x² + 5] / h Definition of derivative
(x² + 2 · x · h + h² - 5 - x² + 5) / h Perfect square trinomial
(2 · x · h + h²) / h Associative, commutative and modulative properties / Existence of additive inverse
2 · x + h Distributive, commutative and associative properties / Definition of division / Existence of multiplicative inverse
2 · x h = 0 / Result
The first derivative of the function f(x) = x² - 5 is equal to f'(x) = 2 · x.
To learn more on derivatives: brainly.com/question/25324584
#SPJ1
It is 15 because 5 times 3 is 15